Auditor-Provided Tax Services: The Effects of a Changing Regulatory Environment - Omer, Thomas C.; Bedard, Jean C.; Falsetta, Diana (The Accounting Review, 2006)
This study investigates auditor-provided tax services from 2000 to 2002, during which fees paid to auditors for nonaudit services (NAS) were disclosed, but separate disclosure of tax service fees was voluntary. We examine changes in the market for tax NAS in 2002, as Congress debated possible prohibition of these services. Using the Heckman MLE procedure to control for selection bias in tax fee disclosure, we find that a strong pre-2002 positive association between tax fees and higher than expected audit fees weakened significantly in 2002, suggesting that some companies paying high audit fees reduced or terminated auditor-provided tax services in 2002. Our findings also suggest that auditor-provided tax services were reduced among new or short-tenure clients. Controlling for tax complexity, we also find some evidence that early “returns” (i.e., tax rate reductions) to companies from auditorprovided tax services were reduced in 2002. Finally, results of our selection model imply that the decision to voluntarily disclose fees paid to the auditor for tax services is positively associated with tax complexity and auditor tenure, and negatively associated with the proportion of NAS fees to total fees. Overall, our findings imply significant change in auditor-provided tax services prior to 2003, when separate disclosure of auditor-provided tax service fees was mandated.